2004
DOI: 10.1111/j.1600-6143.2004.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Endotoxin Monoclonal Antibodies are Protective against Hepatic Ischemia/Reperfusion Injury in Steatotic Mice

Abstract: Steatotic mice are particularly susceptible to hepatic ischemia/reperfusion injury compared with their lean littermates. We have previously demonstrated that livers of mice having a spontaneous mutation in the leptin gene (ob/ob), resulting in global obesity and liver steatosis, are ATP depleted, are endotoxin sensitive, and do not survive (I/R) injury. We hypothesize that administration of an anti-LPS monoclonal antibody (mAb) prior to initiation of I/R would be protective from that insult. Steatotic mice (ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…At 24 h, all lean animals were alive, regardless of the UCP2 phenotype. Survival in the ob/ob WT group was 30%, which was consistent with our previously published studies (30,31). Animal survival of 83% in the UCP2 KO ob/ob group was greater than the ob/ob control group (Fig.…”
Section: Characterization Of Lean and Steatotic Ucp2supporting
confidence: 81%
“…At 24 h, all lean animals were alive, regardless of the UCP2 phenotype. Survival in the ob/ob WT group was 30%, which was consistent with our previously published studies (30,31). Animal survival of 83% in the UCP2 KO ob/ob group was greater than the ob/ob control group (Fig.…”
Section: Characterization Of Lean and Steatotic Ucp2supporting
confidence: 81%
“…It is also noteworthy that Kupffer cells did not get activated (based on the lack of TNF-α secretion) in spite of the hepatocellular damage. It is therefore likely that Kupffer cell activation in vivo depends on the presence of exogenous factors, such as gut-derived endotoxin (25), which were not present in our culture system. Literature data also show that complement activation plays a key role in the postischemic activation of Kupffer cells in vivo (28).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that fatty livers exhibit serious microcirculatory disturbances after ischemia-reperfusion (21)(22)(23). Furthermore, there is evidence of a greater inflammatory response in fatty livers after transplantation (15), and treatments that reduce the inflammatory response, such as heat shock (24) and endotoxin antibodies (25), improve survival of fatty livers. None of these studies can identify the primary or triggering event leading to hepatic failure, as the inflammatory and circulatory changes may or may not be secondary to other earlier damage mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Since the extent of steatosis is positively associated with the extent of IRI (7,8,39,40), and the C3 activation product C3adesArg (also known as acylation-stimulating protein) is involved in the regulation of lipid metabolism (41,42), a possible explanation for the reduced level of hepatic IRI seen in C3 Ϫ/Ϫ mice is that C3 Ϫ/Ϫ mice develop less liver steatosis. However, following a 4-wk high fat diet (60% calories from fat), we detected no significant quantitative or qualitative differences in steatosis between wt and C3 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%